Pengaruh Efikasi Diri terhadap Kecemasan Akademik dalam Mata Pelajaran Matematika Siswa MTs Negeri 1 Pontianak - Aisah Eka Fitriani; Widya Lestari; Rizki Fitlya (Lembaga Pengembangan Kinerja Dosen, 2025)
Mathematics education is a cornerstone in developing students’ critical and analytical thinking skills. This study aimed to examine the effect of self-efficacy on academic anxiety among students of MTs Negeri 1 Pontianak. A quantitative correlational design was employed with 148 students selected via proportional stratified random sampling. Data were collected using the Self-Efficacy Questionnaire for Mathematics (SEQ-M, 20 items) and an adapted 18-item State-Trait anxiety Inventory. Content validity was established by expert panels and reliability coefficients were α = 0.931 for self-efficacy and α = 0.965 for anxiety. Inferential analyses included Kolmogorov–Smirnov normality tests, scatterplot linearity assessments, Pearson correlation, and simple linear regression. Results indicated a significant negative correlation between self-efficacy and academic anxiety (r = –0.438; p < 0.001). The regression coefficient of –0.609 shows that each unit increase in self-efficacy reduces academic anxiety by 0.609 points. Self-efficacy accounted for 19.2% of the variance in anxiety levels (R² = 0.192). Descriptive findings revealed most students scored at moderate levels of self-efficacy (69.1%) and anxiety (86.4%). These outcomes support Bandura’s social cognitive theory, emphasizing belief in one’s capabilities as a buffer against negative emotional responses in mathematics. Practical implications include designing mastery-oriented learning activities, providing targeted positive feedback, and implementing coping strategies and emotion-regulation training. Future research should investigate moderating factors such as social support and self-regulated learning, and adopt qualitative approaches to capture students’ subjective experiences.